2013
DOI: 10.1038/modpathol.2012.159
|View full text |Cite
|
Sign up to set email alerts
|

Detection and significance of human papillomavirus, CDKN2A(p16) and CDKN1A(p21) expression in squamous cell carcinoma of the larynx

Abstract: While a strong etiologic relationship between human papillomavirus and a majority of oropharyngeal squamous cell carcinomas has been established, the role of human papillomavirus in non-oropharyngeal head and neck carcinomas is much less clear. Here, we investigated the prevalence and clinicopathologic significance of human papillomavirus and its reported biomarkers, CDKN2A(p16) and CDKN1A(p21), in laryngeal squamous cell carcinomas in patients treated either with primary surgery and postoperative radiation or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 37 publications
10
88
1
1
Order By: Relevance
“…In the same study by Sethi et al [20] it was confirmed that HPV positivity (in large part HPV16), was associated with improved survival and that the survival advantage of HPV-positivity was limited to oropharyngeal sites. Thus, in the absence of evidence for a prognostic role of HPV testing outside of the oropharynx and metastatic neck lymph nodes, these locations may not need HPV-ISH testing unless histologic and/or clinical features otherwise suggest HPV related cancers [21,22]. Utility of low risk HPV testing in head and neck tumors, if any, should also be addressed in future guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…In the same study by Sethi et al [20] it was confirmed that HPV positivity (in large part HPV16), was associated with improved survival and that the survival advantage of HPV-positivity was limited to oropharyngeal sites. Thus, in the absence of evidence for a prognostic role of HPV testing outside of the oropharynx and metastatic neck lymph nodes, these locations may not need HPV-ISH testing unless histologic and/or clinical features otherwise suggest HPV related cancers [21,22]. Utility of low risk HPV testing in head and neck tumors, if any, should also be addressed in future guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last three decades, the high-risk HPV genotypes (hrHPV) have been confirmed as the major etiologic factor of the subset of oropharyngeal SCC, dominating in the western part of the world [14,15]. The significance of hrHPV infection in the development of tumours in oral cavity, hypopharynx and larynx needs to be additionally elucidated [1,2,[16][17][18]. Controversial data on hrHPV DNA prevalence in hypopharyngeal and laryngeal SCC has been published; prevalence varied considerably, from 5 to 60% [4,19,20].…”
Section: Etiopathogenesis Of Conventional Squamous Cell Carcinoma Sumentioning
confidence: 99%
“…Thus only integrated and transcriptionally active forms of hrHPV contribute in HPV-related carcinogenesis. HPV E6 and E7 oncoproteins are now established as standard biomarkers for oncogenic activity of hrHPVs, together with more than 70% positivity of p16 protein in tumour cells [4,18,19,23,24]. HPVrelated laryngeal and hypopharyngeal SCC is histologically mostly non-keratinizing SCC, but focally may be also keratinizing.…”
Section: Etiopathogenesis Of Conventional Squamous Cell Carcinoma Sumentioning
confidence: 99%
“…It is also easy to perform and interpret. However, outside of the oropharynx, p16 overexpression loses specificity for transcriptionally-active HPV among head and neck SCCs [21]. In addition, approximately 20 % of aggressive cutaneous head and neck SCCs may show diffuse p16 positivity that is unrelated to high-risk HPV, including in their lymph node metastases [22].…”
Section: Squamous Cell Carcinoma Of Unknown Primary In the Era Of Hummentioning
confidence: 99%